ANALISIS RISIKO RANTAI PASOK PESTISIDA PADA PT. AGRICON - Fany Annisa Agusti; Marimin; Heti Mulyati (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
One solution to increase agricultural production is to overcome pests and diseases by using pesticides, which has an influence on pesticides’ availability. Therefore, it is necessary to analyse the performance and risks that arise in the pesticide supply chain. This study aimed to identify and analyse supply chain mechanisms and the performance of pesticide supply chain, and to identify and analyse risks of pesticide supply chain. The Van der Vorst method was used to analyse the structure of supply chain networks, supply chain business processes, supply chain management, and supply chain resources. The results of performance measurement using SCOR model showed that there were still around 0.61% of orders that were not fully fulfilled; the order fulfillment cycle time was 12 days; the upside supply chain flexibility matrix was ​​three days; and the upside supply chain adaptability matrix was ​​11.72%. Based on these results, the performance value of pesticide supply chain was 52.69% and falls into bad (unacceptable) category. These results indicate that there were still performance attributes that were not optimal. There were still lost of opportunities because the company targets were not fulfilled, which had an impact on profit loss. Risk identification using the FMEA-HOR 1 method, from 40 risk events and 24 risk agents, 10 priority of risk agents were obtained that needed to be mitigated so that the pesticides supply chain could run effectively and efficiently. Keywords : pesticides, supply chain mechanisms, performance, risk